Deskripsi Pengembangan Keprofesian Berkelanjutan Guru Matematika - Ahmad Nizar Rangkuti; Roimah Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The purpose of this study was to describe the continuous professional development of mathematics teachers at SMPN 6 Panyabungan which includes aspects of self-development, scientific publications, and innovation works. The data collection method used consisted of observation, interviews, and document studies. Data analysis used descriptive qualitative analysis method which aims to describe how the continuous professional development of mathematics teachers at SMP Negeri 6 Panyabungan and how to deal with problems faced in carrying out continuous professional development of mathematics teachers. The results of the study concluded that in carrying out the Continuing Professional Development (PKB) mathematics teachers there were several problems, namely the lack of a given quota, ignorance of Continuing Professional Development (PKB) and the lack of a teacher's intention to participate in Continuing Professional Development (PKB).